Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12885-020-07370-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumor quiescence: elevating SOX2 in diverse tumor cell types downregulates a broad spectrum of the cell cycle machinery and inhibits tumor growth

Abstract: Background Quiescent tumor cells pose a major clinical challenge due to their ability to resist conventional chemotherapies and to drive tumor recurrence. Understanding the molecular mechanisms that promote quiescence of tumor cells could help identify therapies to eliminate these cells. Significantly, recent studies have determined that the function of SOX2 in cancer cells is highly dose dependent. Specifically, SOX2 levels in tumor cells are optimized to promote tumor growth: knocking down or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…At present, further breakthroughs have been made in the experimental study and analysis of the relationship between the expression, mechanism, regulatory mechanism, and disease of RBC immune function. dependent kinase inhibitor [16][17][18]. Cell cycle regulation is a complex biological process, which is related to the biological efficacy of protooncogenes and tumor suppressor genes.…”
Section: Regulating the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, further breakthroughs have been made in the experimental study and analysis of the relationship between the expression, mechanism, regulatory mechanism, and disease of RBC immune function. dependent kinase inhibitor [16][17][18]. Cell cycle regulation is a complex biological process, which is related to the biological efficacy of protooncogenes and tumor suppressor genes.…”
Section: Regulating the Immune Systemmentioning
confidence: 99%
“…In evolution, cells change and form a series of regulatory mechanisms to ensure the accurate and orderly exchange of the cell cycle. There are mainly three types of molecules related to cell cycle regulation: cyclin, cyclin-dependent kinase (CDK), cyclin-dependent kinase inhibitor [ 16 18 ]. Cell cycle regulation is a complex biological process, which is related to the biological efficacy of protooncogenes and tumor suppressor genes.…”
Section: Tumor Cell Cyclementioning
confidence: 99%
“…SOX2 is clearly implicated in promoting lineage plasticity in prostate cancer, and multiple groups demonstrated an association between expression of SOX2 and neuroendocrine genes with onset of the neuroendocrine prostate cancer (NEPC) cancer phenotype [ 38 43 ]. A role for SOX2 as an oncogene is further supported by multiple studies demonstrating SOX2-mediated changes in cell growth, invasion, and chemoresistance across multiple tumor types [ 6 , 17 , 44 48 ]. Further, we and others have shown that SOX2 is sufficient to enable castration-resistant tumor growth and resistance to the AR antagonist enzalutamide [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 96%
“…For example, the introduction of SOX2 in prostate cancer induces stem-like characteristics but uses different metabolic pathways and interacts with different target gene products. The oncogenic role of SOX2 is confirmed further by several studies exhibiting SOX2 dependent alteration of cell growth, invasion ability, and chemo-resistant activity beyond tumor types [ 103 , 104 ]. de Wet et al demonstrated that most target genes of SOX2 regulation in prostate cancer are non-overlapping with targets of SOX2 in human ESCs, and identified different cis elements within what appear to be similar target genes.…”
Section: Perspective On the Therapeutic Use Of Biomarkersmentioning
confidence: 78%